2004
DOI: 10.1249/01.mss.0000142309.29139.22
|View full text |Cite
|
Sign up to set email alerts
|

One-Mile Run/Walk and Body Mass Index of an Ethnically Diverse Sample of Youth

Abstract: These data suggest 1) disparities in MRW exist among ethnic groups, after controlling for confounders; and 2) the variation observed in MRW is similar to those observed for physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…This finding is consistent with that of Beets et al (23), who reported a similar trend in all California students in 2002. Participation in vigorous activity is higher in Whites (67%) compared with Blacks (54%) and Hispanics (60%), and decreases with advancing grade.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with that of Beets et al (23), who reported a similar trend in all California students in 2002. Participation in vigorous activity is higher in Whites (67%) compared with Blacks (54%) and Hispanics (60%), and decreases with advancing grade.…”
Section: Discussionsupporting
confidence: 93%
“…Our data corroborate prior studies such as the California Children Healthy Eating and Exercise Practices Survey (calCHEEPS), where 32% of 4 th and 5 th graders were overweight or obese (24). When comparing the prevalence of overweight/obesity, our data for Non-Hispanic Whites and Asians are similar to those reported for all California students in 2002, and our data for Hispanics and African-Americans indicated higher prevalence rates than corresponding estimates for the state (23). This is of interest, given the high socio-economic status of the cohort as a whole, and agrees with prior data that even in higher socio-economic strata, obesity risk is increasing.…”
Section: Discussionsupporting
confidence: 81%
“…12 The non-linear shape of BMI trajectories is shown by the time 29 parameter is similar to charts of BMI of French children 30 and more recently in charts for British children and youth. 31 The natural history of BMI is similar to that for body fat, a steep rise during infancy with a peak at 9 months of age, followed by a fall until age 6 years and then a second rise, which lasts until adulthood.…”
Section: Discussionsupporting
confidence: 70%
“…• 38%-39% (Zephier, Himes, & Story, 1999) • 20%-21% (Caballero et al, 2003) • 33% (Beets & Pitetti, 2004) Overweight (BMI ≥95% tile) • 18%-22% (Zephier et al, 1999) • 27%-31% (Caballero et al, 2003) • 19% (Beets & Pitetti, 2004) …”
Section: Adultsmentioning
confidence: 99%